Pengaruh Gelling Agent terhadap Sifat Fisik Gel Ekstrak Daun Ruku - Ruku (Ocimum tenuiflorum L.) - Wida Ningsih; Sherli Ramadhani; Fitri Wahyuni; Afdhil Arel (Universitas Muhammadiyah Klaten, 2025)
Gel is one of the preparations used topically which is a semi-solid preparation consisting of a suspension of small inorganic particles and large organic particles penetrated by liquid. Gel formation requires additional materials called gelling agents. There are three types of gelling agents, derived from natural polymers, synthetic polymers and semisynthetic polymers. The gelling agent material is a natural polymer such as sodium alginate; semisynthetic polymers are sodium carboxymethylcellulose and synthetic polymers are carbomer 940. Purpose: This study aims to see the quality of ruku-ruku leaf extract with variations of gelling agents. The types of natural polymers used are Method: making ruku-ruku leaf extract by maceration method with 70% ethanol solvent and formulated into a gel preparation. The gel of ruku-ruku leaf extract was evaluated for its physical quality, cycling test and conducting antibacterial activity testing by agar diffusion in wells. Results: The quality of the physical properties of the gel produced from the three polymers of different origins showed a stable gel and met the requirements for the quality of the gel preparation. Conclusion: The type of gelling agent does not affect the quality of the gel preparation.